SUBSTITUSI SARI UBI JALAR UNGU DAN SARI BUAH MARKISA PADA PEMBUATAN PERMEN JELLY - Hadi Kusumah, Slamet (Jurnal Ilmiah Dozen Globalindo, 2021)
The use of sweetpotato is still limited for food and a little for the food industry raw material. This study aims to determine the organoleptic value of jelly candy with substitutions of purple sweetpotato juice and passion fruit juice with different percentages. The research method used was experimental using a completely randomized design. The factors studied were the number of substitutes for purple sweet potato juice used with a concentration (25%, 50%, 75%) and passion fruit juice with a concentration (5%, 10%, 15%). The treatment was carried out twice. The test conducted was an organoleptic test covering parameters of aroma, color, taste, and texture which were assessed by 25 untrained panelists. The data obtained were then analyzed using Ms. Excel and given a descriptive study. The results showed that jelly candy substituted with purple sweet potato juice by 50% and passion fruit juice by 15% had the aroma, color, taste and texture with the highest organoleptic value. The aroma of jelly candy is the aroma of passion fruit juice but it still smells of sweet potato. Jelly candy colors are bright and very attractive. The resulting jelly candy flavor is sweet and has a purple passion fruit flavor. The resulting jelly candy texture is chewy, elastic, and soft.